2018
DOI: 10.1002/smll.201802994
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of IR820‐ and Ce6‐Based Versatile Micelle for Single NIR Laser–Induced Imaging and Dual‐Modal Phototherapy

Abstract: triggered by near-infrared (NIR) lightexcited photothermal agents [10] while PDT causes the cell death by photosensitizers generating highly cytotoxic reactive oxygen species (ROS) upon light excitation. [11][12][13] With distinct mechanisms of action, the integration of PTT and PDT into one nanoplatform holds great potential to achieve highly efficient cancer therapy. [14][15][16] However, in such combined therapy, two different excitation wavelengths are usually required for the activation of PTT and PDT, [1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 60 publications
0
42
0
Order By: Relevance
“…IR820 has been used to label polyethylenimine on delivered DNA so that the labeled construct can be monitored in vivo with noninvasive NIR‐I imaging . Studies on IR820 and IR820‐labeled bioconjugates have clearly confirmed its value and prospects in NIR‐I imaging and image‐guided drug or photothermal therapy . An IR820‐based agent was recently designed for naked‐eye and NIR I fluorescence dual‐mode imaging…”
Section: Introductionmentioning
confidence: 99%
“…IR820 has been used to label polyethylenimine on delivered DNA so that the labeled construct can be monitored in vivo with noninvasive NIR‐I imaging . Studies on IR820 and IR820‐labeled bioconjugates have clearly confirmed its value and prospects in NIR‐I imaging and image‐guided drug or photothermal therapy . An IR820‐based agent was recently designed for naked‐eye and NIR I fluorescence dual‐mode imaging…”
Section: Introductionmentioning
confidence: 99%
“…The application of nanoparticles incorporating IR820 in cancer PTT/PDT and NIR imaging and PAI has also been extensively investigated ( Tables 6 and ) . For instance, Huang et al incorporated IR820 in ferritin nanocages, demonstrating the ability of these nanostructures to accumulate at the tumor and image it through PAI .…”
Section: Nanomaterials Incorporating Heptamethine Cyanines For Cancermentioning
confidence: 99%
“…11. Micelle carrier, the stable micelles, may exhibit improved photothermal efficiency toward cancer cells for both in vitro and in vivo studies [15].…”
Section: Common Nanoformulation Systems Loaded With Herbal Active Ingmentioning
confidence: 99%